Gender diversity in the boardroom and corporate cash holdings: The moderating effect of investor protection - Wan Adibah Wan Ismail; Khairul Anuar Kamarudin; Namrata Gupta; Iman Harymawan (Risks, 2022)
This paper investigates whether gender diversity in the boardroom is associated with corporate cash holdings and whether investor protection moderates the effect of corporate board gender diversity on corporate cash holdings. Using 20,750 firm-year observations from 33 countries, our analyses show that firms with high levels of corporate board gender diversity exhibit low corporate cash holdings. Furthermore, firms in countries with high levels of investor protection have low corporate cash holdings. Moreover, the negative association between board gender diversity and corporate cash holdings is weaker in high-level investor protection countries than in low-level investor protection countries. Our results are robust to various specification tests, such as the endogeneity issue, weighted least-squares regression, the global economic crisis effect, alternative measures for corporate cash holdings, and various country-level institutional features. Taken together, the findings reveal that board gender diversity and investor protection have significant influences on corporate cash holdings. These findings have significant implications for politicians, governments, and regulators in devising policies relating to the United Nations Sustainable Development Goal (SDG Number 5) on achieving gender equality and women empowerment.
Keywords: G38; G18; M41; M43; M4; 330; board gender diversity; corporate cash holdings; investor protection